The Evaluation of Pension Reforms in the Public Sector: A Case Study of the Paris Subway Drivers - Touria Jaaidane; Robert J. Gary-Bobo (Center for Economic Studies and ifo Institute (CESifo), 2015)
To evaluate pension reforms in public services, we put forward a simple criterion, the actuarial cost of a worker, per year of service. This measure of cost is the expected, discounted sum of net real wages and pension benefits, earned by a worker over his entire life cycle, divided by the number of years of service. We show the possibility of reforms such that (i), the actuarial cost of a worker per year of service is reduced, (ii) the utility of workers does not decrease and (iii) the pension fund deficits do not increase. Workers can willingly postpone retirement in exchange for increased final salaries and pensions. Present and future public subsidies may at the same time be reduced. We propose a quantitative analysis of the 2008 reform of the Paris Metro pensions. Focusing on the case of train drivers, we show that the reform should save public funds, but only in the long run. During a long transition period, the reform is likely to end up with larger State subsidies to the pension scheme. The reform can be interpreted as a deal between public authorities and insiders at the expense of recent recruits. A reform preserving the public budget from an outright increase in social costs could have been both technically feasible and politically acceptable.
Keywords: H55; J26; J45; 330; pensions; reform public sector; transportation workers